HUBUNGAN PANJANG PENIS DENGAN INDEKS MASSA TUBUH PADA ANAK USIA 6-8 TAHUN - Ikram Syah Maulana; Robby Kalew; Josepina Mainase; Mellyana K. Atmanegara (Fakultas Kedokteran Universitas Pattimura, 2019)
Penis that has a short size will be a problem for parents. Usually the size of the penis is associated with obesity and considered that the size of the penis will become normal again after losing weight, therefore this study aims to determine whether there is a relationship of penis length with body mass index in children aged 6-8 years old in elementary school in Sirimau sub-district. The approach used in this research is cross-sectional conducted in SD Xaverius C, SD Kalam Kudus and SD Negeri 93 Ambon in June-August 2017. The number of respondents in this study are 85 children taken by consecutive sampling technique. Penis length is measured using